Does the European Union endanger Poland and Poland’s reasons of state? Theoretical and practical aspects (Economic and Political Thought, 2017)
The article aims to answer the question that is nowadays often asked duringscientific discussions and among politicians: Does the European Unionendanger Poland and Poland’s national interests? Under the influence ofcriticism of globalisation and its negative effects as well as the mega-crisis,which the EU has not been able to overcome for a long time, populism andnationalistic tendencies are growing in Europe and in the world. As a result,extreme right wing parties glorifying the essence of a national state andnegating the sense of the existence of the European Union, which cannotcope with the financial and economic crisis, migration, leadership, axiology,international terrorism and many other problems, come to power. Globalisationand the EU are deemed to be the sources of those problems, which manycountries in Europe and in the world face. The article presents theoreticaland practical aspects of the European Union specificity and its significance ininternational relations, especially for national states – exemplified by Poland– in the realities of the contemporary, dynamically changing world. The mainthesis is a statement that the EU does not directly endanger a member stateand its national interests. However, in some circumstances, for the benefit ofthe majority of its members, it may limit and limits its political sovereigntyand international activeness. As a result, it makes a member state act in a waythat is in conflict with its national interest and the reason of state.